Clinical findings associated with N‐terminal pro‐B‐type natriuretic peptide measurement in dogs and cats attending first opinion veterinary practices. (23rd September 2021) - O'Shaughnessy, Sarah; Crawford, India; Arsevska, Elena; Singleton, David; Hughes, David; Noble, Peter‐John; Hezzell, Melanie
Abstract: Background: Clinical findings associated with N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) measurement in dogs and cats in primary practice, and their relevance to published measurement indications, have not been described. Methods: Using electronic health record data collected by the Small Animal Veterinary Surveillance Network, appointments in which NT‐proBNP was measured were identified using keyword‐based text filtering. For these appointments, clinical findings were manually identified from each patient's clinical narrative (CN) and their frequencies described. Results: CNs of 3510 appointments (357 dogs and 257 cats) from 99practices were evaluated. The most frequently recorded clinical findings in dogs were: heart murmur ( n = 147, 41.2% (95% confidence interval (CI) = 36.1%–46.3%), coughing ( n = 83, 23.2% (95% CI = 18.8%–27.6%)) and panting ( n = 58, 16.2% (95% CI = 12.4%–20.0%)) and in cats: heart murmur ( n = 143, 55.6% (95% CI = 49.5%–61.7%)), suspected thromboembolism ( n = 88, 34.2% (95% CI = 28.4%–40.0%)) and weight loss ( n = 53, 20.6% (95% CI = 15.7%–25.5%)). Dyspnoea and tachypnoea were infrequently reported in dogs ( n = 29, 8.1% (95% CI = 5.3%–10.9%) and n = 21, 5.9% (95% CI = 3.5%–8.3%), respectively) and cats ( n = 26, 10.1% (95% CI = 6.4%–13.8%) and n = 36, 14.0% (95% CI = 9.8%–18.2%), respectively). Conclusion: Clinical findings referable to cardiac disease were recorded contemporaneously with NT‐proBNP measurement and suggested both published and other indications (coughing (in dogs and cats), and serial measurements and thromboembolism (in cats)) for testing.